Jaringan Komunikasi Untuk Gerakan Sosial: Studi Kasus pada Komunitas Transpuan Yogyakarta untuk Akses E-KTP: Communication Networks for Social Movement: Case Study in the Yogyakarta’s Transwomen Community for E-KTP Access - Vidiadari, Irene Santika (Anterior Jurnal, 2025)
The transwomen group is a marginalized gender minority, excluded from various aspects of life, including politics, economics, society, and culture. This marginalization is further exacerbated by the fact that access to public services now requires an electronic ID card (e-KTP). To fulfill their civil rights, transpuan people must network and mobilize collectively. This study examines the communication efforts undertaken by the transpuan community in Yogyakarta to gain access to the e-KTP. The research was conducted through focus group discussions (FGDs) and interviews with members of the transpuan community in Yogyakarta (IWAYO). The findings indicate that vulnerable groups, such as transpuan communities, must establish cross-issue coalitions to create a collective communication network. This collective action becomes a source of strength for marginalized groups to achieve their goals. The community also engaged with government institutions, academics, and non-governmental organizations (NGOs) to advocate for the empowerment of community members and the fulfillment of their civil rights. Internally, IWAYO fostered communication using various strategies, including establishing sub-communities at nine community locations across Yogyakarta, holding social gatherings (arisan), organizing pesantren (group prayer), and conducting regular meetings.